(untitled) (Pedagogy of Higher and Secondary Education, 2007)
This work is devoted to the learning and rising the moved quality of schoolchildren. With the help of the investigation in conditions of the Extreme North was found out that more than 90% of the pupils (5-llth forms) according to the level showed by physical exercises the quality of knowledge and the moved quality development in a complex are at the very low stage.